Determinants of Professional Potential in Youth Soccer Players : A Multidimensional Performance Analysis - Riga Mardhika; Ramadhany Hananto Puriana; Santika Rentika Hadi; I Gede Dharma Utamayasa (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi FKIP Universitas PGRI Mahadewa Indonesia bekerjasama dengan Asosiasi Prodi Olahraga Perguruan Tinggi PGRI (APOPI), 2026)
This study aimed to analyze the performance data of youth soccer players and identify key factors influencing their professional potential. The research focused on examining the contribution of physical, technical, and psychological variables to the development of young athletes and their prospects for achieving professional-level performance. A quantitative cross-sectional design was employed involving 60 youth soccer players aged 14-18 years from three soccer academies in East Java, Indonesia. Data were collected through standardized physical performance tests (30 m sprint, Illinois agility test, and VO₂Max), technical skill assessments (passing accuracy, dribbling speed, and shooting precision), and psychological questionnaires measuring training motivation and discipline. The collected data were analyzed using descriptive statistics, Pearson correlation, multiple regression analysis, and exploratory factor analysis (EFA) to identify significant predictors and underlying performance factors. Results: The results showed that VO₂Max, dribbling speed, passing accuracy, and training motivation significantly contributed to the professional potential of youth soccer players (p < 0,05). The regression model explained approximately 62-66% of the variance in professional potential, indicating that a combination of physical, technical, and psychological components plays a crucial role in athlete development. Factor analysis revealed three dominant performance dimensions: physical capacity, technical skills, and psychological readiness, which together accounted for 68,4% of the total variance. Conclusions: The findings highlight the importance of a multidimensional evaluation approach in youth soccer talent identification and development. Integrating physical, technical, and psychological assessments can support more objective and data-driven decision-making in athlete development programs and enhance the effectiveness of youth soccer training systems.